Android-Based Digital Teaching Materials as Online Learning in New Normal Era to Improve Physics HOTS for High School Students - Mardiana, Nana; Prayogi, Satria Yudha; S, Sukartika; Haslina, Siti; Harizan, Md (Journal of Natural Science and Integration, 2022)
The current research was carried out to develop android-assisted digital teaching materials in new normal era in order to improve students' HOTS in physics learning activities. Similarly, the study seeks to realize innovative, creative and up-to-date Physics learning activities. The present development research employs the ADDIE systematic learning model, (1) analysis; (2) design; (3) development; (4) implementation; and (5) evaluation. The data analysis is a type of qualitative-quantitative method by assessing the quality of the product developed by competent experts, such as lecturers and teachers in accordance with the field of physics study presented in the form of numbers. The outputs generated from this research are Android-assisted digital teaching materials as an online learning solution for the new normal era to improve the HOTS of students with the values of digital teaching materials (e-modules) on temperature and heat materials as a whole classified as “Very Eligible” considered 91.6%.Keywords: digital teaching materials, android, covid-19, physics, HOTS